Osterwalder's business model canvas: Its genesis, features, comparison, benefits and limitations - Donovan A. McFarlane (Westcliff University, 2017)
This essay is a brief exploration of Osterwalder's Business Model Canvas. The author discusses the genesis of the Business Model Canvas, the unique features of the approach of the Business Model Canvas, and then compares the Business Model Generation to other business model approaches. Finally, the benefits and/or limitations of using Osterwalder's business model canvas in the context of the author's organization - a higher education organization, are examined.